The Correlation between Students' Motivation and Learning Achievement of the Eleventh Graders of SMK 1 PSKD Jakarta - Invokavit, Bulan Meilany (JET (Journal of English Teaching), 2017)
AbstractThe objective of this study was to find out the correlation between students’ motivation and their English learning achievement at SMK 1 PSKD. This study used quantitative method. The instrument used was a 17 Likert-scaled questionnaires. The score of English learning achievement was taken from the report final exam of eleventh grade. The respondents of thisstudy were XI AK and AP at SMK 1 PSKD. The total number of respondents was 38 students. This study used a survey or correlation study. Data analysis showed there was positive correlation between students’ motivation and their English learning achievement. The number of correlation coefficient was 0.324 which means that the correlation coefficient was weak. The coefficient of determination was 10.5% which means such amount contributed on English learning achievement while 89.5% was other undefined factors. Keywords: Students’ Motivation, English Learning Achievement